Spatial variation of myriapods along an urban-rural gradient in Skopje city and it surrounding - Gjorgievska, Aleksandra; Prelik, Dana; Hristovski, Slavčo; Stoev, Pavel (Macedonian Journal of Ecology and Environment, 2008)
This investigation aims to analyze the influence of urbanization on millipedes and centipedes (Myriapoda) in three different localities (urban, suburban and rural) along an urban-rural gradient in the city of Skopje and its surrounding, as well as to determine the structure of the community. The material was collected monthly, during one year period (07.2004–07.2005), by method of pitfall traps placed along a transect. Qualitative and quantitative analysis, seasonal dynamics and spatial variation along the gradient were determined. The presence of four families: Julidae, Scolopendridae, Scutigeridae and Lithobiidae was registered. In total 28,72 ind./trap were found, from which the most abundant were Julidae (27,20 ind./trap). There were significant changes (at the 95% level of confidence) in the abundance of myriapods during the year and along the gradient.